Urban emotions and the making of the city
1 online resource.
Keywords: "This book brings together a vibrant interdisciplinary mix of scholars - from anthropology, architecture, art history, film studies, fine art, history, literature, linguistics, and urban studies - to explore the role of emotions in the making and remaking of the city. By asking how urban boundaries are produced through and with emotion; how emotional communities form and define themselves through urban space; and how the emotional imaginings of urban spaces impact on histories, identities and communities, the volume advances our understanding of "urban emotions" into discussions of materiality, power and embodiment across time and space"--